2011
DOI: 10.4318/tjg.2011.0150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of providing information to the patient about upper gastrointestinal endoscopy on the patient’s perception, compliance and anxiety level associated with the procedure

Abstract: Amaç: Endoskopi gibi tan› ifllemleri hastalarda anksiyeteye neden olmaktad›r. Anksiyetenin azalt›lmas› için en uygun giriflim hastan›n ifllem hakk›nda bilgilendirilmesidir. Çal›flmam›z endoskopi hastalar›n›n bilgilendirilmesinin hastan›n ifllemi alg›lamas›na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
5
25
1
Order By: Relevance
“…The study conducted by S. Pehlivan at al. showed that providing verbal or written information to patients before performing endoscopic examination significantly affects their submission to the examination, reduces anxiety and increases patient satisfaction with this kind of examination (1). Similar results were found in a study by M. Qureshi at al.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The study conducted by S. Pehlivan at al. showed that providing verbal or written information to patients before performing endoscopic examination significantly affects their submission to the examination, reduces anxiety and increases patient satisfaction with this kind of examination (1). Similar results were found in a study by M. Qureshi at al.…”
Section: Discussionsupporting
confidence: 79%
“…Endoscopic examinations of the digestive tract are commonly used safe and secure methods for the diagnosis and treatment of the gastrointestinal tract diseases (1,2). Procedures include diagnostic or therapeutic upper and lower endoscopy (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher levels of anxiety lead to physiologic fluctuations as increased blood pressure and pulse. Also anxiety prior to endoscopy can increase the requirement for sedation, analgesics and increased length of time during procedure in addition to increase cost [3] and [4].…”
Section: Introductionmentioning
confidence: 99%